The law and economics of class actions - Langenfeld, James (Emerald, 2014)
This book focuses on the changing landscape of class action law and its interaction with the economic analysis of key issues in class actions. Articles examine the elements of class action law from diverse viewpoints, featuring defendant and plaintiff perspectives, concerning domestic and international law, and written by lawyers and economists.
Includes index.
Keywords: Law and economics.; Class actions (Civil procedure) -- Economic aspects -- United States.; Antitrust law -- Economic aspects -- United States.; elektronické knihy; electronic books